Proteolysis, Cell Adhesion, Chemotaxis, and Invasiveness Are Regulated by the u-PA-u-PAR-PAI-1 System - Blasi, Francesco (Thrombosis and Haemostasis, 1999)
High levels of urokinase-type plasminogen activator (u-PA), of its inhibitor (plasminogen activator inhibitor (PAI)-1), or of its receptor (u-PAR, CD87) are strong prognostic indicators of relapse in human cancers. In addition, many in vitro data show that u-PA, PAI-1, and u-PAR have a profound influence on cell migration. This set of molecules regulates surface proteolysis, cell adhesion, and chemotaxis through different mechanisms. Binding to u-PAR strongly stimulates the activation of pro-u-PA and, hence, of plasminogen, resulting in localized production of the broad-spectrum serine protease, plasmin, which can digest extracellular matrix proteins or activate latent motogenic factors. Chemotaxis is induced through an u-PA-dependent conformational change in u-PAR, which uncovers a very potent chemotactic epitope(s) that acts through a pertussis toxin-sensitive step and activates intracellular tyrosine kinases. In addition, cell adhesion is affected by an u-PA-dependent exposure of u-PAR epitope(s), which interact with vitronectin (VN), integrins, and caveolin, thus modifying the substrate specificity. Thus, u-PA binding can transform u-PAR from a simple receptor for u-PA into a pleiotropic ligand for other surface molecules.All of these processes are regulated by the u-PA inhibitor, PAI-1. Inhibition of cell adhesion and migration by PAI-1 on VN occurs because the same region of VN is required for interaction with PAI-1, u-PAR, and integrins. PAI-1, however, also affects u-PAR occupancy by triggering the internalization of the u-PA-u-PAR complex, the degradation of u-PA, and the recycling of free u-PAR. Available data suggest that cells respond to a “stop” signal, due to the PAI-1-dependent internalization and degradation of u-PA. Cells also respond to a “go” signal through the stimulation of surface-proteolysis, exposure of chemotactic epitopes, and recycling of u-PAR to novel surface positions. Finally, cells respond to a “pause” signal through transient u-PAR-dependent adhesion stages, thus shifting the cells between an “adhesion-mode” and a “migration-mode.”